Kinetic, mechanistic, and active site studies of copper metal-organic framework catalyzed nitric oxide generation from S-nitrosoglutathione in water and blood plasma - Tuttle, Robert Reeves, author; Reynolds, Melissa M., advisor; Finke, Richard, committee member; Crans, Debbie, committee member; Popat, Ketul, committee member (Colorado State University. Libraries, 2021)
Catalytic generation of nitric oxide (NO) from endogenous sources by copper-based materials at the surfaces of implanted medical devices improves device performance by promoting vasodilation and inhibiting bacterial adhesion. Oxidation of the endogenous tripeptide S-Nitrosoglutathione (GSNO) to release NO is catalyzed by the copper-based metal-organic framework (MOF) H3[(Cu4Cl)3(BTTri)8] (CuBTTri) in the presence of glutathione (GSH). MOFs are solid-state, crystalline, porous materials composed of metal cation nodes and organic linkers forming three-dimensional structures. MOFs have generated interest as catalysts because of their unparalleled tunability via synthesis (compared to other solids), well-defined structures, coordinatively unsaturated metal sites, and high surface areas. Mechanistic insight into MOF catalysts promises to allow for the directed design of next-generation catalysts via leveraging synthetic tunability. However, because necessary studies to propose reliable reaction mechanisms are rarely reported for MOF catalysts, mechanistic understanding is lacking in the field. This Dissertation works toward a reaction mechanism of CuBTTri catalyzed GSNO to NO conversion in water in the presence of GSH. The strategies used to better understand this mechanism can also generate mechanistic knowledge in other MOF catalysis systems. Chapter I provides a discussion of NO release catalyzed by soluble and insoluble Cu-based species focusing on CuBTTri. Chapter I also introduces MOFs as catalysts and explains the requirements to propose a reliable reaction mechanism. Chapters II and III focus on the development of monitoring methods to quantify [GSNO], [GSH], and [glutathione disulfide] (the other main reaction product, GSSG) in real time in H2O and blood plasma. 1H nuclear magnetic resonance (NMR) and ultraviolet-visible (UV-VIS) spectroscopies can together effectively monitor the NO release reaction. The observation of an inverse dependence on added GSH for CuBTTri versus solvated Cu ions for NO generation shows that the two catalysts operate via different reaction mechanisms. Chapter III shows how the monitoring method in H2O reported in Chapter II can be extended to track the reaction in blood plasma. The observed GSNO to NO reaction stoichiometry is effectively identical in H2O and blood plasma, which indicates that the mechanism does not change in vivo versus the model biological solvent H2O. Hence, mechanistic findings in this dissertation for NO generation in water are likely biologically applicable. Chapter IV establishes the catalytically active Cu sites in CuBTTri for GSNO to NO conversion. Studies comparing the reaction rate (-d[GSNO]/dt) to particle size revealed that ~100% of the observed catalysis is caused by Cu atoms on the external surfaces of CuBTTri particles. Kinetic poisoning studies of CuBTTri particles with potassium cyanide (KCN) and 3,3',3''-phosphanetriyltris (benzenesulfonic acid) trisodium salt (TPPTS) showed that the active sites are kinetically uniform. Fourier transform infrared spectroscopic analysis of CN-poisoned CuBTTri detected Cu(CN)3 and Cu(CN) sites, which correspond to the idealized metal-terminated CuBTTri crystal structure. Size-selective kinetic poisoning studies of CuBTTri using TPPTS measured the active site density to be (1.3 ± 0.4)% of total Cu atoms in 600 ± 400 nm CuBTTri particles. Active site density was used to calculate a normalized turnover frequency for CuBTTri to make informed inter-catalyst comparisons. Chapter V presents the rate law and proposed mechanism for CuBTTri catalyzed GSNO to NO conversion. Four other competing, minimalistic mechanistic hypotheses were considered and disproven. The mechanism proposed is a CuII to formally CuIII redox mechanism with two proton-coupled electron transfer elementary steps. The proposed mechanism exhibits a derived rate law which matches the experimental rate law, has elementary steps which sum to the observed reaction stoichiometry, and provides a reasonable driving force for S-N bond homolysis in GSNO. Future computational and laboratory experiments suggested by the proposed mechanism promise to yield a level of mechanistic understanding for CuBTTri which has traditionally not been achievable for solid-state catalysts.
Keywords: CuBTTri; GSNO; NO conversion